2022
DOI: 10.1111/psq.12797
|View full text |Cite
|
Sign up to set email alerts
|

Presidential Strategies in Statements of Administration Policy

Abstract: Presidents routinely employ Statements of Administration Policy (SAPs) to inform Congress about the executive's thoughts and position on pending legislation. Such statements are used for a variety of purposes, including bill promotion, suggesting changes, issuing veto threats, and addressing perceived threats to traditional powers. While SAPs have been identified as an important vehicle for interbranch communication and a key source of insight into presidential preferences, many questions remain as to how pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Word counts are a measure of how much a president has to say to Congress about a bill, with lengthier veto messages signaling that a president spent more time and attention on an issue. Prior presidential research has used message length as a measure of presidential attention (Ostrander & Sievert, 2022) and indicative of attempting persuasion (Collins & Eshbaugh‐Soha, 2019, pp. 37–38).…”
Section: Veto Messages As Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Word counts are a measure of how much a president has to say to Congress about a bill, with lengthier veto messages signaling that a president spent more time and attention on an issue. Prior presidential research has used message length as a measure of presidential attention (Ostrander & Sievert, 2022) and indicative of attempting persuasion (Collins & Eshbaugh‐Soha, 2019, pp. 37–38).…”
Section: Veto Messages As Datamentioning
confidence: 99%
“…In both cases, the differences are significant at the p < 0.01 level in a two‐sample t test. While word counts are a blunt measure, past studies of presidential communications have indicated that length is a measure of a president's attention to an issue as well as an indication that they are attempting to persuade (Collins & Eshbaugh‐Soha, 2019; Ostrander & Sievert, 2022). Lower word counts may imply that presidents felt less need to justify their actions when using pocket vetoes because Congress cannot directly reply with an override.…”
Section: Analyzing Executive Argumentsmentioning
confidence: 99%